Development of student worksheets based on local wisdom in the Riau Islands Province using realistic mathematics education to facilitate mathematical reasoning abilities - Yodiatmana, Yodiatmana; Murni, Atma; Hutapea, Nahor Murani (Universitas Maritim Raja Ali Haji, 2024)
This research is motivated by students' low mathematical reasoning ability due to conventional teaching methods and the lack of learning resources that support students' reasoning skills. Local wisdom-based student worksheets were developed using the Realistic Mathematics Education approach to address this issue. Local wisdom from Tanjungpinang, Riau Islands, such as Otak-otak and Batik Gonggong, was used as the context for learning Systems of Linear Equations in Two Variables. The research method used is Research and Development (R&D) with a 4D development model (define, design, develop, disseminate). The instruments for assessing validity and practicality were expert validation questionnaires and student response questionnaires using a Likert scale. The effectiveness instrument used was a set of four essay questions. Data obtained on the Likert scale were analyzed using the Method of Successive Interval (MSI). Validation results showed that the student worksheets were categorized as valid, with an average expert validation percentage of 76.2%. Practicality tests yielded an average percentage of 77.59% (small group) and 67% (field test), both categorized as practical. The effectiveness test results showed an average score of 79.8 in the high category, and the mathematical reasoning ability test was deemed effective, with a classical mastery level of 90%. This study highlights the effectiveness of local wisdom-based worksheets using the Realistic Mathematics Education approach to facilitate students' mathematical reasoning skills and encourages teachers to integrate local wisdom into student worksheets.